The Race of Sound : Listening, Timbre, and Vocality in African American Music - Eidsheim, Nina Sun, 1975- (Book collections on Project MUSE., 2019)
In The Race of Sound Nina Sun Eidsheim traces the ways in which sonic attributes that might seem natural, such as the voice and its qualities, are socially produced. Eidsheim illustrates how listeners measure race through sound and locate racial subjectivities in vocal timbre--the color or tone of a voice. Eidsheim examines singers Marian Anderson, Billie Holiday, and Jimmy Scott as well as the vocal synthesis technology Vocaloid to show how listeners carry a series of assumptions about the nature of the voice and to whom it belongs. Outlining how the voice is linked to ideas of racial essentialism and authenticity, Eidsheim untangles the relationship between race, gender, vocal technique, and timbre while addressing an undertheorized space of racial and ethnic performance. In so doing, she advances our knowledge of the cultural-historical formation of the timbral politics of difference and the ways that comprehending voice remains central to understanding human experience, all the while advocating for a form of listening that would allow us to hear singers in a self-reflexive, denaturalized way.